Noncardiac Chest Pain: Epidemiology, Natural Course and Pathogenesis - Fass, Ronnie (Korean Society of Neurogastroenterology and Motility, 2011)
Noncardiac chest pain is defined as recurrent chest pain that is indistinguishable from ischemic heart pain after a reasonable workup has excluded a cardiac cause. Noncardiac chest pain is a prevalent disorder resulting in high healthcare utilization and significant work absenteeism. However, despite its chronic nature, noncardiac chest pain has no impact on patients' mortality. The main underlying mechanisms include gastroesophageal reflux, esophageal dysmotility and esophageal hypersensitivity. Gastroesophageal reflux disease is likely the most common cause of noncardiac chest pain. Esophageal dysmotility affects only the minority of noncardiac chest pain patients. Esophageal hypersensitivity may be present in non-GERD-related noncardiac chest pain patients regardless if esophageal dysmotility is present or absent. Psychological co-morbidities such as panic disorder, anxiety, and depression are also common in noncardiac chest pain patients and often modulate patients' perception of disease severity.